Partisipasi GenBI Dalam Upaya Pengembangan BI Corner Universitas Sebelas Maret Berbasis Digital Bidang Perbankan - Sri Anawati; Sri Utari; Argyo Demartoto (Universitas Wijaya Kusuma Surabaya, 2023)
Purpose Research. The BI Corner is the gateway for information about the economy and BI's duties, GenBI is the long arm. The purpose of writing is to find out the participation of GenBI in the development of a digital-based BI Corner in the banking sector and the supporting factors that hinder it. Research Method. The research method is mixed methods, exploratory, action research. Collecting data by observation, interviews, FGD and documentation. Results. GenBI's participation in efforts to develop BI Corner UNS, namely socialization, promotion on social media; Added a digital collection application; Provide e-journal website, e-book, QR Code; Digitize the GenBI final project; Collaborating GenBI-lecturers-users; Creating profile videos, selection of library ambassadors. Supporting factors are the availability of infrastructure; Leadership support; Modern design; free wifi; Availability of librarians; Ease of reading, borrowing collections. The inhibiting factor is that the collection is not up to date; Lack of care; There is no GenBI-Library collaboration, digital facilities and development plans; Management and utilization have not been maximized. Conclusions. The impact of GenBI's participation is to have a digital-based reading Corner; Improving branding, the welfare of the academic community, the community by implementing business practices; Raising awareness regarding digital collections in the banking sector, enhancing BI's positive image.